Canopy inequity persists beyond the urban core, but its underlying drivers vary across a large metropolitan region - Lindsay E. Darling; Dexter H. Locke; Christine R. Rollinson; Roshanak (Roshi) Nateghi; Robert T. Fahey; Anita T. Morzillo; Brady S. Hardiman (Urban Forestry & Urban Greening, 2026)

Turning a new leaf: Social and land use drivers of urban tree canopy change in the Chicago Metropolitan Area 2010–2017 - Jackson D. Lyall; Lindsay E. Darling; Dexter H. Locke; Brady S. Hardiman (Urban Forestry & Urban Greening, 2025)

Variation in patterns of production and water-use efficiency among agroecosystems - Olivia L. Hajek; Nicole E. Kaplan; Shefali Azad; Philip A. Fay; Makki Khorchani; Amanda M. Nelson; Adam P. Schreiner-McGraw; Lori J. Abendroth; Claire Baffaut; John Baker; Brandon T. Bestelmeyer; Elizabeth H. Boughton; et al. (Science of The Total Environment, 2025)

Sequence‐Based Multi Ancestry Association Study Reveals the Polygenic Architecture of Varroa destructor Resistance in the Honeybee Apis mellifera - Sonia E. Eynard; Fanny Mondet; Benjamin Basso; Olivier Bouchez; Yves Le Conte; Benjamin Dainat; Axel Decourtye; Lucie Genestout; Matthieu Guichard; François Guillaume; Emmanuelle Labarthe; Barbara Locke; et al. (Molecular Ecology, 2025)
Honeybees, Apis mellifera , have experienced the full impacts of globalisation, including the recent invasion by the parasitic mite Varroa destructor , now one of the main causes of colony losses worldwide. The strong selection pressure it exerts has led some colonies to develop defence strategies conferring some degree of resistance to the parasite. Assuming these traits are partly heritable, selective breeding of naturally resistant bees could be a sustainable strategy for fighting infestations. To characterise the genetic determinism of varroa resistance, we conducted the largest genome wide association study performed to date on whole genome sequencing of more than 1500 colonies on multiple phenotypes linked to varroa resistance of honeybees. To take into account some genetic diversity of honeybees, colonies belonging to different ancestries representing the main honeybee subspecies in Western Europe were included and analysed both as separate populations and combined in a meta‐analysis. The results show that varroa resistance is substantially heritable and polygenic: while 60 significant associations were identified, none explain a substantial part of the trait genetic variance. Overall our study highlights that genomic selection for varroa resistance is promising but that it will not be based on managing a few strong effect mutations and rather use approaches that leverage the genome wide diversity of honeybee populations. From a broader perspective, these results point the way towards understanding the genetic adaptation of eusocial insects to parasite load.

Echocardiographic and pathologic identification of an aorto-left atrial fistula secondary to infective endocarditis in a canine patient - K. Iuliani; A. Lawler; D. Schrope; E. Locke (Journal of Veterinary Cardiology, 2024)

Spatial and Temporal Patterns of Nitrogen Mobilization in Residential Lawns - Amanda K. Suchy; Peter M. Groffman; Lawrence E. Band; Jonathan M. Duncan; Arthur J. Gold; J. Morgan Grove; Dexter H. Locke; Laura Templeton; Ruoyu Zhang (Ecosystems, 2023)

Conceptualizing social-ecological drivers of change in urban forest patches - Lea R. Johnson; Michelle L. Johnson; Myla F. J. Aronson; Lindsay K. Campbell; Megan E. Carr; Mysha Clarke; Vincent D’Amico; Lindsay Darling; Tedward Erker; Robert T. Fahey; Kristen L. King; Katherine Lautar; et al. (Urban Ecosystems, 2021)

Fossil Giraffidae (Mammalia, Artiodactyla) from Lee Adoyta, Ledi-Geraru, and Late Pliocene Dietary Evolution in Giraffids from the Lower Awash Valley, Ethiopia - John Rowan; Ellis M. Locke; Joshua R. Robinson; Christopher J. Campisano; Jonathan G. Wynn; Kaye E. Reed (Journal of Mammalian Evolution, 2017)

Smoking status, usual adult occupation, and risk of recurrent urothelial bladder carcinoma: data from The Cancer Genome Atlas (TCGA) Project - Amber N. Wilcox; Debra T. Silverman; Melissa C. Friesen; Sarah J. Locke; Daniel E. Russ; Noorie Hyun; Joanne S. Colt; Jonine D. Figueroa; Nathaniel Rothman; Lee E. Moore; Stella Koutros (Cancer Causes & Control, 2016)

A Systematic Assessment of the Use of Platelet-Rich Plasma in Spinal Fusion - Benjamin D. Elder; Christina Holmes; C. Rory Goodwin; Sheng-Fu Lo; Varun Puvanesarajah; Thomas A. Kosztowski; John E. Locke; Timothy F. Witham (Annals of Biomedical Engineering, 2015)

Diazinon and Permethrin Mitigation Across a Grass–Wetland Buffer - M. T. Moore; R. Kröger; M. A. Locke; R. E. Lizotte; S. Testa; C. M. Cooper (Bulletin of Environmental Contamination and Toxicology, 2014)

Vulnerability and diet breadth predict larval and adult parasite diversity in fish of the Bothnian Bay - Sean A. Locke; David J. Marcogliese; E. Tellervo Valtonen (Oecologia, 2014)

Responses of Phytoplankton and Hyalella azteca to Agrichemical Mixtures in a Constructed Wetland Mesocosm - Richard E. Lizotte; Sam Testa; Martin A. Locke; R. Wade Steinriede (Archives of Environmental Contamination and Toxicology, 2013)

Altered patterns of multiple recombinant events are associated with nondisjunction of chromosome 21 - Tiffany Renee Oliver; Stuart W. Tinker; Emily Graves Allen; Natasha Hollis; Adam E. Locke; Lora J. H. Bean; Reshmi Chowdhury; Ferdouse Begum; Mary Marazita; Vivian Cheung; Eleanor Feingold; Stephanie L. Sherman (Human Genetics, 2012)

The scopolamine model as a pharmacodynamic marker in early drug development - Robert A. Lenz; Jeffrey D. Baker; Charles Locke; Lynne E. Rueter; Eric G. Mohler; Keith Wesnes; Walid Abi-Saab; Mario D. Saltarelli (Psychopharmacology, 2012)

Growth line deposition and variability in growth of two circumpolar bivalves (Serripes groenlandicus, and Clinocardium ciliatum) - William G. Ambrose; Paul E. Renaud; William L. Locke; Finlo R. Cottier; Jørgen Berge; Michael L. Carroll; Benjamin Levin; Stuart Ryan (Polar Biology, 2012)

Effects of Vegetation in Mitigating the Toxicity of Pesticide Mixtures in Sediments of a Wetland Mesocosm - Richard E. Lizotte; Matthew T. Moore; Martin A. Locke; Robert Kröger (Water, Air, & Soil Pollution, 2011)

Role of Vegetation in a Constructed Wetland on Nutrient–Pesticide Mixture Toxicity to Hyalella azteca - Richard E. Lizotte; Matthew T. Moore; Martin A. Locke; Robert Kröger (Archives of Environmental Contamination and Toxicology, 2011)

Female choice and the relatedness of mates in the guppy (Poecilia reticulata) - Trevor E. Pitcher; F. Helen Rodd; Locke Rowe (Genetica, 2008)

Diazinon Mitigation in Constructed Wetlands: Influence of Vegetation - M. T. Moore; C. M. Cooper; S. Smith; R. F. Cullum; S. S. Knight; M. A. Locke; E. R. Bennett (Water, Air, & Soil Pollution, 2007)

Local Enhancement in Mud-Puddling Swallowtail Butterflies (Battus philenor and Papilio glaucus) - G.W. Otis; B. Locke; N.G. McKenzie; D. Cheung; E. MacLeod; P. Careless; A. Kwoon (Journal of Insect Behavior, 2006)

Land Use Influences and Ecotoxicological Ratings for Upper Clinch River Tributaries in Virginia - B. A. Locke; D. S. Cherry; C. E. Zipper; R. J. Currie (Archives of Environmental Contamination and Toxicology, 2006)

Profiling penciclovir susceptibility and prevalence of resistance of herpes simplex virus isolates across eleven clinical trials - R. T. Sarisky; T. H. Bacon; R. J. Boon; K. E. Duffy; K. M. Esser; J. Leary; L. A. Locke; T. T. Nguyen; M. R. Quail; R. Saltzman (Archives of Virology, 2003)